Re-assessing the growth parameters for the razor clam, Ensis siliqua, from Scottish electrofishing grounds using external shell marks and oxygen isotope validation - Chloe Blackman; Lynda Blackadder; Elizabeth M. Harper; Clive Fox (Fisheries Research, 2025)

How well do connectivity tools agree over the full life cycle? A case study of Irish Sea plaice Pleuronectes platessa Linnaeus , 1758 - Audrey J. Geffen; Richard D. M. Nash; Clive J. Fox (Journal of Fish Biology, 2025)
Adult plaice in the Irish Sea have distinct traits that reflect the spawning locations that could suggest a number of different populations. However, do connectivity pathways support this concept? Different tools are directed at measuring exchange or connectivity between different life‐history stages, and the challenge is to integrate the signals to obtain full life‐cycle estimates. Collectively, the different methods reveal stable connectivity between known spawning and nursery grounds, with sufficient exchange to maintain a single population with weak genetic structure.

An Assessment of Demersal Elasmobranch Occurrence and Associated Habitats Using an Autonomous Underwater Vehicle ( AUV ) - Jonathon Taylor; John A. Howe; James Thorburn; Clive J. Fox; Christopher McGonigle; Petra Rybanska (Marine Ecology, 2025)
To implement effective management and conservation strategies, an understanding of the spatial ecology, habitat preferences and movement of demersal elasmobranchs is required. This study combines a photographic survey obtained from an autonomous underwater vehicle (AUV) with existing bathymetric data to help understand elasmobranch ecology within the Firth of Lorn, western Scotland. This area is within the Loch Sunart to Sound of Jura Marine Protected Area (MPA) and designated for the protection of the critically endangered flapper skate ( Dipturus intermedius ). Two areas of seabed were surveyed using an AUV in water depths of 110–165 m southwest of the Isle of Kerrera. Eight surveys were conducted in total, four in each area. Each area was surveyed twice over 2 days in October 2020 and twice in 2 days in May June 2021. One day used bait on the seabed (October) whilst all the others had no bait. For each survey, the AUV travelled 17 km at a height of 2 m above the seabed in a lawnmower pattern providing 0.5 km 2 photographic coverage for ~2 h per survey. Five elasmobranch species, two scyliorhinids ( Scyliohinus canicula and Galeus melastomus ) and three rajiformes ( D. intermedius , Raja clavata and Leucoraja naevus ), were identified from a total of 43 k seabed photographs. In total 42 individual animals and 7 egg cases were observed. Although the AUV had short survey times and small study areas the results are encouraging for AUVs being a useful tool in understanding elasmobranch ecology.

Skin barrier function for regulatory skin absorption tests and effects on testosterone and sucrose absorption - Thomas Brackin; Heather Gayes; Ian Johnson; David Fox; Clive Roper (Toxicology in Vitro, 2024)

A review of new and existing non-extractive techniques for monitoring marine protected areas - Ryan McGeady; Robert M. Runya; James S. G. Dooley; John A. Howe; Clive J. Fox; Andrew J. Wheeler; Gerard Summers; Alexander Callaway; Suzanne Beck; Louise S. Brown; Gerard Dooly; Chris McGonigle (Frontiers in Marine Science, 2023)
Ocean biodiversity loss is being driven by several anthropogenic threats and significant efforts are required to halt losses and promote healthy marine ecosystems. The establishment of a network of Marine Protected Areas (MPAs) can help restrict damaging activities and have been recognised as a potential solution to aid marine conservation. When managed correctly they can deliver both ecological and socio-economic benefits. In recent times, MPA designations have increased rapidly while many countries have set future MPA targets for the decades ahead. An integral element of MPA management is adequate monitoring that collects data to assess if conservation objectives are being achieved. Data acquired by monitoring can vary widely as can the techniques employed to collect such data. Ideally, non-destructive and non-invasive methods are preferred to prevent damage to habitats and species, though this may rule out a number of traditional extractive sampling approaches such as dredges and trawls. Moreover, advances in ocean observation technologies enable the collection of large amounts of data at high resolutions, while automated data processing is beginning to make analyses more logistically feasible and less time-consuming. Therefore, developments to existing marine monitoring techniques and new emerging technologies have led to a diverse array of options when choosing to implement an MPA monitoring programme. Here, we present a review of new and existing non-extractive techniques which can be applied to MPA monitoring. We summarise their capabilities, applications, advantages, limitations and possible future developments. The review is intended to aid MPA managers and researchers in determining the suitability of available monitoring techniques based on data requirements and site conditions.

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

Retrospective analysis of the influence of environmental drivers on commercial stocks and fishing opportunities in the Irish Sea - Jacob W. Bentley; Natalia Serpetti; Clive J. Fox; Johanna J. Heymans; David G. Reid (Fisheries Oceanography, 2020)
Irish Sea fisheries have undergone considerable change in recent years following the decline of commercially important finfish stocks and their slow response to management's recovery plans. In 2015, the fishing industry called for a holistic exploration into the impact of environmental change and food web effects to identify the drivers underpinning stock dynamics. In this study, we identify correlations between large‐scale climatic indicators, temperature, primary and secondary productivity, and fish recruitment in the Irish Sea and incorporate them into an Ecopath with Ecosim food web model co‐created by scientists and fishers. Negative correlations were found between the North Atlantic Oscillation winter index (NAOw) and large zooplankton abundance and between the Atlantic Multidecadal Oscillation (AMO) and the recruitment of cod ( Gadus morhua ) and whiting ( Merlangius merlangus) . Using correlation analyses to direct the addition of environmental drivers to the Irish Sea ecosystem model improved the models fit against observed biomass and catch data and revealed the indirect impacts of environmental change as mitigated through trophic interactions. Model simulations suggest that historic environmental change suppressed the overall production of commercial finfish, limiting opportunities for the fishing industry, whilst also dampening the rate of stock recovery despite marked reductions in fishing effort. These results suggest that failure to account for ecosystem information may lead to misconceived expectations and flawed fisheries management; therefore, there is a need to operationalize ecosystem information through management procedures to support fisheries advice.

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Fishing impact and environmental status in E uropean seas: a diagnosis from stock assessments and ecosystem indicators - Didier Gascuel; Marta Coll; Clive Fox; Sylvie Guénette; Jérome Guitton; Andrew Kenny; Leyla Knittweis; J Rasmus Nielsen; Gerjan Piet; Tiit Raid; Morgane Travers‐Trolet; Samuel Shephard (Fish and Fisheries, 2016)
Stock‐based and ecosystem‐based indicators are used to provide a new diagnosis of the fishing impact and environmental status of E uropean seas. In the seven European marine ecosystems covering the B altic and the N orth‐east A tlantic, (i) trends in landings since 1950 were examined; (ii) syntheses of the status and trends in fish stocks were consolidated at the ecosystem level; and (iii) trends in ecosystem indicators based on landings and surveys were analysed. We show that yields began to decrease everywhere (except in the B altic) from the mid‐1970s, as a result of the over‐exploitation of some major stocks. Fishermen adapted by increasing fishing effort and exploiting a wider part of the ecosystems. This was insufficient to compensate for the decrease in abundance of many stocks, and total landings have halved over the last 30 years. The highest fishing impact took place in the late 1990s, with a clear decrease in stock‐based and ecosystem indicators. In particular, trophic‐based indicators exhibited a continuous decreasing trend in almost all ecosystems. Over the past decade, a decrease in fishing pressure has been observed, the mean fishing mortality rate of assessed stocks being almost halved in all the considered ecosystems, but no clear recovery in the biomass and ecosystem indicators is yet apparent. In addition, the mean recruitment index was shown to decrease by around 50% in all ecosystems (except the B altic). We conclude that building this kind of diagnosis is a key step on the path to implementing an ecosystem approach to fisheries management.

Distribution and trophic links of gelatinous zooplankton on Dogger Bank, North Sea - Jessica R. Frost; Anneke Denda; Clive J. Fox; Charles A. Jacoby; Rolf Koppelmann; Morten Holtegaard Nielsen; Marsh J. Youngbluth (Marine Biology, 2012)

Spawning of North Sea fishes linked to hydrographic features - PETER MUNK; CLIVE J. FOX; LOES J. BOLLE; CINDY J. G. Van DAMME; PETTER FOSSUM; GERD KRAUS (Fisheries Oceanography, 2009)
Spawning of fishes takes place across a wide area of the North Sea. However, more intense spawning is seen in restricted areas, indicating that such areas present favorable conditions. To update information on fish spawning in the North Sea and analyze potential linkages to hydrographic characteristics, an internationally coordinated survey was conducted in the winter/spring of 2004. Oblique hauls for fish eggs and larvae and vertical profiles of temperature and salinity were carried out at 393 stations across the entire North Sea. The hydrography was strongly influenced by the interfacing of water masses of different salinity, and frontal zones were seen along all coastal areas and off the Dogger and Fisher Banks. Total abundances of eggs and larvae, including fish species such as cod, haddock, plaice, long rough dab and sandeel, peaked in the vicinity of the frontal areas. Hence our findings indicate that the main spawning locations of fish are linked to recurrent hydrographic features such as salinity fronts. Such a linkage may provide survival advantages, as the fronts present favorable feeding conditions, and the related physical processes may confine egg and larval dispersal and transport them towards suitable nursery habitats.

North Sea cod and climate change – modelling the effects of temperature on population dynamics - Robin A. Clark; Clive J. Fox; David Viner; Matthew Livermore (Global Change Biology, 2003)
In order to examine the likely impacts of climate change on fish stocks, it is necessary to couple the output from large‐scale climate models to fisheries population simulations. Using projections of future North Sea surface temperatures for the period 2000–2050 from the Hadley General Circulation Model, we estimate the likely effects of climate change on the North Sea cod population. Output from the model suggests that increasing temperatures will lead to an increased rate of decline in the North Sea cod population compared with simulations that ignore environmental change. Although the simulation developed here is relatively simplistic, we demonstrate that inclusion of environmental factors in population models can markedly alter one's perception of how the population will behave. The development of simulations incorporating environment effects will become increasingly important as the impacts of climate change on the marine ecosystem become more pronounced.